Rural schools in Mendoza: tensions and opportunities due to the 2015 curriculum reform (Praxis Educativa, 2025)
This article recovers part of the research process of a doctoral thesis in progress. It seeks to analyze the current curricular reform for the secondary level in 2015 in the province of Mendoza, Argentina, focusing on rural secondary schools. Prioritizes discussion of the decisions that were made during the research process regarding the sample, methodology, and analysis, and reflects on what these imply (and say) about the epistemological and theoretical framework. The conclusions show findings linked to emerging categories from the analysis of the information collected in the field work, which can open doors to other research or future studies linked to rural education.
Keywords: Rural education - Educational system - State and education - Educational policy - Secondary education